Changes and Challenges in Inpatient Mental Health Care During the First Two High Incidence Phases of the COVID-19 Pandemic in Germany – Results From the COVID Ψ Psychiatry Survey - Hauke Felix Wiegand; Anna-Lena Bröcker; Mandy Fehr; Niklas Lohmann; Birgit Maicher; Nikolaus Röthke; Mike Rueb; Paula Wessels; Moritz de Greck; Andrea Pfennig; Stefan Unterecker; Oliver Tüscher; et al. (Frontiers in Psychiatry, 2022)
Psychiatric inpatient treatment, an important pillar of mental health care, is often of longer duration in Germany than in other countries. The COVID-19 pandemic called for infection prevention and control measures and thereby led to shifts in demand and inpatient capacities. The Germany-wide COVID Ψ Psychiatry Survey surveyed department heads of German psychiatric inpatient institutions. It assessed changes in utilization during the first two high incidence phases of the pandemic (spring 2020 and winter 2020/21) and also consequences for care, telemedicine experiences, hygiene measures, treatment of patients with mental illness and co-occuring SARS-CoV-2, and coercive measures in such patients. A total of n = 71 psychiatric departments (of 346 contacted) participated in the survey. The results showed a median decrease of inpatient treatment to 80% of 2019 levels and of day hospital treatment to 50% (first phase) and 70% (second phase). Reductions were mainly due to decreases in elective admissions, and emergency admissions remained unchanged or increased in 87% of departments. Utilization was reduced for affective, anxiety, personality, and addiction disorders but appeared roughly unaffected for psychotic disorders. A lack of integration of patients into their living environment, disease exacerbations, loss of contact, and suicide attempts were reported as problems resulting from reduced capacities and insufficient outpatient treatment alternatives. Almost all departments (96%) treated patients with severe mental illness and co-occurring SARS-CoV-2 infection. The majority established special wards and separate areas for (potentially) infectious patients. Telephone and video consultations were found to provide benefits in affective and anxiety disorders. Involuntary admissions of persons without mental illness because of infection protection law violations were reported by 6% of the hospitals. The survey showed high adaptability of psychiatric departments, which managed large capacity shifts and introduced new services for infectious patients, which include telemedicine services. However, the pandemic exacerbated some of the shortcomings of the German mental health system: Avoidable complications resulted from the lack of cooperation and integrated care sequences between in- and outpatient sectors and limited options for psychiatric hospitals to provide outpatient services. Preventive approaches to handle comparable pandemic situations in the future should focus on addressing these shortcomings.